Analisis Pencitraan Lembaga Pemerintah Oleh Humas Dalam Pemberitaan Media Online Nasional - Afwan Syahril Manurung; Suhendri Suhendri; Wahyunisa Wahyunisa; Hazrina Syahirah Putri; Syifa Urrahmah (Universitas Merdeka Malang, 2026)
This research analyzes the government public relations strategy in shaping institutional image through national online media. Digital media has become the primary means of forming public opinion, where narrative and news framing significantly influence public perception. Using a descriptive qualitative approach and content analysis of news from Kompas.com, Detik.com, and CNNIndonesia.com, this study identifies communication patterns, media relations effectiveness, as well as supporting and hindering factors in image building. The results contribute to strengthening the role of public relations in establishing a positive and credible institutional image in the digital age.